High-strength anti-aging PVC plastic particles and preparation method thereof
Patent Information
- Application Number
- CN202611185263.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]为了解决现有技术中小分子抗老化剂易迁移流失、大量添加导致电缆料力学及电气性能下降,以及共混体系界面易受老化破坏等技术问题,本发明提出了一种高强度抗老化的PVC塑胶颗粒及其制备方法
[0035]1.本发明利用三嗪环桥接制备功能化纳米二氧化硅,将受阻胺基团和受阻酚基团固载于纳米二氧化硅表面,克服了电缆在长期发热和紫外照射下传统小分子助剂易挥发、易析出的缺陷。经测试,紫外老化1000h后拉伸强度保持率>93%。
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a high-strength, anti-aging PVC plastic granule and its preparation method. Background Technology
[0002] Polyvinyl chloride (PVC) is widely used in building materials, pipes, and cable sheaths due to its excellent flame retardancy, chemical resistance, and good electrical insulation. Especially in applications such as outdoor charging pile cables and overhead optical cables, PVC cable materials need to withstand long-term ultraviolet radiation, high and low temperature cycles, and weathering. However, under the long-term effects of outdoor light, heat, and oxygen, pure PVC material is prone to dechlorination, leading to molecular chain breakage or cross-linking. Macroscopically, this manifests as yellowing and brittleness, a significant decrease in insulation performance and mechanical strength—a phenomenon known as aging—which can easily cause safety accidents such as leakage and short circuits.
[0003] To address aging issues, existing technologies typically add small-molecule hindered amine light stabilizers and antioxidants to PVC formulations. However, excessive addition of small-molecule stabilizers can deteriorate the tensile and impact strength of the material, resulting in an internal plasticizing effect. Furthermore, during cable heating and long-term service, small-molecule stabilizers can easily migrate to the material surface and precipitate, causing blooming. This leads to a decline in anti-aging effects over time, contaminating the cable surface and reducing insulation resistance.
[0004] Meanwhile, chlorinated polyvinyl chloride (PVC) is often introduced to improve heat resistance and mechanical strength. In traditional direct blending processes, the interfacial compatibility between chlorinated PVC and rigid fillers / PVC matrix still needs improvement, and physical blending is insufficient to resist microcrack formation during long-term aging. Based on the above, this invention proposes a high-strength, anti-aging PVC plastic granule and its preparation method. Summary of the Invention
[0005] To address the technical problems in existing technologies, such as the easy migration and loss of small molecule anti-aging agents, the decline in the mechanical and electrical properties of cable materials due to excessive addition, and the susceptibility of the interface of blended systems to aging damage, this invention proposes a high-strength anti-aging PVC plastic granule and its preparation method.
[0006] In a first aspect, the present invention provides a high-strength, anti-aging PVC plastic granule, employing the following technical solution:
[0007] A high-strength, anti-aging PVC plastic granule comprises the following raw materials in parts by weight: 60-80 parts of polyvinyl chloride resin, 20-40 parts of composite chlorinated polyvinyl chloride masterbatch, 5-15 parts of functionalized nano silica, 4-8 parts of impact modifier, 10-20 parts of plasticizer, 3-5 parts of composite stabilizer, and 1-2 parts of lubricant.
[0008] Preferably, the composite chlorinated polyvinyl chloride masterbatch is produced by intensive extrusion of chlorinated polyvinyl chloride, epoxidized natural rubber and zinc stearate in a mass ratio of 100:15-25:1-2.
[0009] Preferably, the chlorinated polyvinyl chloride has a chlorine content of 65-70%.
[0010] Preferably, the mixing and extrusion parameters are: mixing temperature 160-170℃, mixing time 10-15min, and rotor speed 50-70rpm.
[0011] This invention introduces a composite chlorinated polyvinyl chloride masterbatch prepared by premixing chlorinated polyvinyl chloride and epoxidized natural rubber. During the high-temperature aging process of extrusion and subsequent cable service, the trace amounts of hydrogen chloride removed from the chlorinated polyvinyl chloride and polyvinyl chloride can immediately catalyze the ring-opening of the epoxy groups in the epoxidized natural rubber and react chemically with the active sites on the polymer chain segments, thereby acting as an in-situ macromolecular acid absorbent to prevent autocatalytic degradation. At the same time, an elastic cross-linked network is formed between the chlorinated polyvinyl chloride and polyvinyl chloride matrix, enhancing the material's ability to resist environmental stress cracking.
[0012] Preferably, the functionalized nano-silica is modified nano-silica with hindered amine groups and hindered phenolic groups covalently grafted onto its surface through a triazine ring structure.
[0013] Preferably, the functionalized nano-silica is prepared by the following method:
[0014] (1) Dissolve cyanuric chloride in toluene, and add γ-aminopropyltriethoxysilane and the first part of organic acid binder dropwise under an ice-water bath at 0-5℃. After the addition is complete, react for 2-3 hours, then heat the system to 40-50℃, add 4-amino-2,2,6,6-tetramethylpiperidine and the second part of organic acid binder, and react for 4-6 hours. Then heat the system to 80-90℃, add 4-amino-2,6-di-tert-butylphenol and the third part of organic acid binder, and continue the reaction for 8-10 hours. After the reaction is complete, filter to remove the salt precipitate generated in the reaction to obtain the functional modified liquid.
[0015] (2) Put nano-silica into a high-speed mixer equipped with a vacuum pump and condensation recovery device, heat it to 110-120℃ for 10-15 min, keep the temperature constant, and spray deionized water equivalent to 1-3% of the mass of nano-silica into the high-speed mixer while stirring. Then spray the functional modification liquid onto the surface of nano-silica and continue high-speed mixing for 15-20 min. During this process, turn on the vacuum pump to remove the solvent and reaction by-products, cool, and obtain functionalized nano-silica.
[0016] Preferably, in step (1), the organic acid binder is triethylamine.
[0017] Preferably, in step (1), the mass ratio of cyanuric chloride, toluene, γ-aminopropyltriethoxysilane, 4-amino-2,2,6,6-tetramethylpiperidine, 4-amino-2,6-di-tert-butylphenol and the total amount of organic acid binder is 18-20:200:21-23:15-16:21-23:31-35, and the mass ratio of the first part of organic acid binder, the second part of organic acid binder and the third part of organic acid binder is 1:1:1.
[0018] Preferably, in step (1), the dripping refers to the uniform dripping under continuous stirring at 400-600 rpm, and the dripping is completed in 1-2 hours.
[0019] Preferably, in step (2), the average particle size of the nano-silica is 30-50 nm.
[0020] Preferably, in step (2), the mass ratio of nano-silica to functional modification liquid is 1:2-4.
[0021] Preferably, in step (2), the stirring speed is 1500-2000 rpm.
[0022] This invention introduces functionalized nano-silica, using cyanuric chloride as a bridging core, and covalently immobilizes hindered amines and hindered phenols on the surface of the nano-silica. On one hand, the rigid nanocore acts as a physical cross-linking point in the matrix, improving the tensile strength of the cable; on the other hand, the triazine ring possesses excellent heat resistance and rigidity, fixing the photothermal dual anti-aging groups on the surface of the nanoparticles, avoiding the problem of decreased cable insulation caused by the precipitation of small molecule additives, and achieving both mechanical enhancement and long-term anti-aging effects.
[0023] Preferably, the plasticizer is dioctyl terephthalate. Environmentally friendly dioctyl terephthalate has excellent electrical properties, not only with low volatility but also meeting the insulation requirements of cable materials.
[0024] Preferably, the composite stabilizer is a calcium-zinc composite stabilizer. The calcium-zinc composite stabilizer is lead-free, complies with RoHS directive requirements, and synergistically provides excellent initial and long-term thermal stability to the composite chlorinated polyvinyl chloride masterbatch.
[0025] Preferably, the lubricant is a mixture of stearic acid and polyethylene wax in a mass ratio of 1-3:1. The combination of stearic acid as an external lubricant and polyethylene wax as an internal lubricant effectively balances the internal and external lubrication of plastic granules during extrusion, reduces melt viscosity, and prevents material from adhering to the equipment.
[0026] Secondly, the present invention provides a method for preparing high-strength, anti-aging PVC plastic granules, employing the following technical solution:
[0027] A method for preparing high-strength, anti-aging PVC plastic granules includes the following steps:
[0028] S1. By weight, add polyvinyl chloride resin and composite chlorinated polyvinyl chloride masterbatch into a high-speed mixer, heat to 100-110℃, add composite stabilizer and mix to obtain initial mixture;
[0029] S2. Add functionalized nano-silica, impact modifier, plasticizer and lubricant to the initial mixture, and continue to heat to 120-130℃ to mix, to obtain the mixture.
[0030] S3. Transfer the mixture to a cold mixer, cool it to 40-50℃, and then send it to a twin-screw extruder for melt blending, extrusion granulation, cooling and drying to obtain high-strength, anti-aging PVC plastic granules.
[0031] Preferably, in step S1, the mixing parameters are: stirring speed 800-1000 rpm, mixing time 5-10 min.
[0032] Preferably, in step S2, the mixing parameters are: stirring speed 1200-1500 rpm, mixing time 10-15 min.
[0033] Preferably, in step S3, the temperature of each zone of the twin-screw extruder is set as follows: zone 1 150-160℃, zone 2 160-170℃, zone 3 170-180℃, die head 175-185℃, screw speed 150-200rpm, and length-to-diameter ratio 36-40:1.
[0034] In summary, the present invention has the following beneficial effects:
[0035] 1. This invention utilizes triazine ring bridging to prepare functionalized nano-silica, immobilizing hindered amine and phenolic groups on the surface of nano-silica, overcoming the defects of traditional small-molecule additives that are prone to volatilization and precipitation under long-term heating and ultraviolet irradiation in cables. Testing showed that the tensile strength retention rate after 1000 hours of ultraviolet aging was >93%.
[0036] 2. This invention introduces a composite chlorinated polyvinyl chloride masterbatch, which captures HCl and performs ring-opening in-situ crosslinking reaction during the processing and aging of epoxidized natural rubber, forming an elastic crosslinking network between chlorinated polyvinyl chloride and polyvinyl chloride matrix, enabling the plastic particles to obtain high impact strength while maintaining high tensile strength.
[0037] 3. The formula used in this invention avoids the damage to the cable surface insulation layer caused by the migration of small molecule additives. The prepared plastic granules have high volume resistivity, which meets the stringent application requirements of outdoor high-standard charging pile cables and special communication cables. Detailed Implementation
[0038] The present invention will be further described in detail below with reference to the embodiments.
[0039] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0040] Among them, the polyvinyl chloride resin: suspension method, grade SG-5, brand Xinfa, purchased from Zibo Mantanghong Trade Co., Ltd.
[0041] Chlorinated polyvinyl chloride: extrusion grade, chlorine content 65-70%, model J-700, brand Hanghao, purchased from Weifang Hanghao New Material Technology Co., Ltd.
[0042] Epoxidized natural rubber: Model ENR-50, brand Juji, purchased from Jining Juji New Materials Co., Ltd.
[0043] Impact modifier: Model ACR401, brand Zhongmai, purchased from Yancheng Zhongmai Rubber & Plastic Products Co., Ltd.
[0044] Calcium-zinc composite stabilizer: Product number JL-539, brand Junlong, purchased from Shijiazhuang Junlong Chemical Products Sales Co., Ltd.
[0045] Polyethylene wax: Model Q-18PE wax, brand Xindongyi, purchased from Wuhan Xindongyi Chemical Co., Ltd.
[0046] Examples 1-3 provide a high-strength, anti-aging PVC plastic granule and its preparation method.
[0047] Example 1
[0048] A high-strength, anti-aging PVC plastic granule comprises the following raw materials in parts by weight: 70 parts of polyvinyl chloride resin, 30 parts of composite chlorinated polyvinyl chloride masterbatch, 10 parts of functionalized nano silica, 6 parts of impact modifier, 15 parts of plasticizer, 4 parts of composite stabilizer, and 1.5 parts of lubricant.
[0049] The composite chlorinated polyvinyl chloride masterbatch is made by adding chlorinated polyvinyl chloride, epoxidized natural rubber and zinc stearate into a mixer in a mass ratio of 100:20:1.5, mixing at a mixing temperature of 165℃ and a rotor speed of 60rpm for 12.5 minutes, and then extruding.
[0050] Functionalized nano-silica was prepared by the following method:
[0051] (1) The mass ratio of cyanuric chloride, toluene, γ-aminopropyltriethoxysilane, 4-amino-2,2,6,6-tetramethylpiperidine, 4-amino-2,6-di-tert-butylphenol and triethylamine was controlled to be 19:200:22:15.5:22:33. The triethylamine was divided into three parts. Cyanuric chloride was dissolved in toluene. γ-aminopropyltriethoxysilane was added dropwise at a uniform rate under continuous stirring at 500 rpm in an ice-water bath at 3°C. The first part of triethylamine was added dropwise over 1.5 hours. After the addition was complete, the reaction was allowed to proceed for 2.5 hours. Then, the system was heated to 45°C, and 4-amino-2,2,6,6-tetramethylpiperidine and the second part of triethylamine were added. After the reaction was allowed to proceed for 5 hours, the system was heated to 85°C, and 4-amino-2,6-di-tert-butylphenol and the third part of triethylamine were added. The reaction was continued for 9 hours. After the reaction was completed, the salt precipitate generated by the reaction was removed by filtration to obtain the functional modified solution.
[0052] (2) Control the mass ratio of nano-silica and functional modification liquid to 1:3. Put nano-silica with an average particle size of 40nm into a high-speed mixer equipped with a vacuum pump and condensation recovery device, heat it to 115℃ for 13min, keep the temperature constant, and spray deionized water equivalent to 2% of the mass of nano-silica into the high-speed mixer under stirring at 1800rpm. Then spray the functional modification liquid onto the surface of nano-silica and continue high-speed mixing for 18min. During this process, turn on the vacuum pump to remove the solvent and reaction by-products, cool, and obtain functionalized nano-silica.
[0053] The plasticizer is dioctyl terephthalate.
[0054] The composite stabilizer is a calcium-zinc composite stabilizer.
[0055] The lubricant is a mixture of stearic acid and polyethylene wax in a mass ratio of 2:1.
[0056] A method for preparing high-strength, anti-aging PVC plastic granules includes the following steps:
[0057] S1. By weight, add polyvinyl chloride resin and composite chlorinated polyvinyl chloride masterbatch into a high-speed mixer, heat to 105°C, add composite stabilizer, control the stirring speed to 900 rpm, mix for 8 minutes to obtain the initial mixture.
[0058] S2. Add functionalized nano-silica, impact modifier, plasticizer and lubricant to the initial mixture, continue to heat to 125℃, control the stirring speed to 1350rpm, mix for 13min to obtain the mixture.
[0059] S3. Transfer the mixture to a cold mixer, cool it to 45°C, and then discharge it into a twin-screw extruder. The temperature settings for each zone of the twin-screw extruder are: Zone 1 155°C, Zone 2 165°C, Zone 3 175°C, and the die head 180°C. The screw speed is 180 rpm, and the length-to-diameter ratio is 38:1. After melt blending, granulate it using a water ring pelletizer. The pelletizing speed is set to 400 rpm. After naturally cooling to room temperature, send it to a fluidized bed for drying at 55°C for 25 minutes to obtain high-strength, anti-aging PVC plastic granules.
[0060] Example 2
[0061] A high-strength, anti-aging PVC plastic granule comprises the following raw materials in parts by weight: 60 parts of polyvinyl chloride resin, 20 parts of composite chlorinated polyvinyl chloride masterbatch, 5 parts of functionalized nano silica, 4 parts of impact modifier, 10 parts of plasticizer, 3 parts of composite stabilizer, and 1 part of lubricant.
[0062] The composite chlorinated polyvinyl chloride masterbatch is made by adding chlorinated polyvinyl chloride, epoxidized natural rubber and zinc stearate into a mixer in a mass ratio of 100:15:1, mixing for 15 minutes at a mixing temperature of 160℃ and a rotor speed of 50rpm, and then extruding.
[0063] Functionalized nano-silica was prepared by the following method:
[0064] (1) The mass ratio of cyanuric chloride, toluene, γ-aminopropyltriethoxysilane, 4-amino-2,2,6,6-tetramethylpiperidine, 4-amino-2,6-di-tert-butylphenol and triethylamine was controlled to be 18:200:21:15:21:31. Triethylamine was divided into three parts. Cyanuric chloride was dissolved in toluene. γ-aminopropyltriethoxysilane and the first part of triethylamine were added dropwise at a constant rate under the conditions of 0℃ ice-water bath and 400rpm stirring. The addition was completed in 2h. After the addition was completed, the system was heated to 40℃ after 3h of reaction. 4-amino-2,2,6,6-tetramethylpiperidine and the second part of triethylamine were added. After 6h of reaction, the temperature was further raised to 80℃. 4-amino-2,6-di-tert-butylphenol and the third part of triethylamine were added. The reaction was continued for 10h. After the reaction was completed, the salt precipitate generated by the reaction was removed by filtration to obtain the functional modified liquid.
[0065] (2) Control the mass ratio of nano-silica and functional modification liquid to 1:2. Put nano-silica with an average particle size of 30nm into a high-speed mixer equipped with a vacuum pump and condensation recovery device, heat it to 110℃ for 15min, keep the temperature constant, and spray deionized water equivalent to 1% of the mass of nano-silica into the high-speed mixer under stirring at 1500rpm. Then spray the functional modification liquid onto the surface of nano-silica and continue high-speed mixing for 20min. During this process, turn on the vacuum pump to remove the solvent and reaction by-products, cool, and obtain functionalized nano-silica.
[0066] The plasticizer is dioctyl terephthalate.
[0067] The composite stabilizer is a calcium-zinc composite stabilizer.
[0068] The lubricant is a mixture of stearic acid and polyethylene wax in a 1:1 mass ratio.
[0069] A method for preparing high-strength, anti-aging PVC plastic granules includes the following steps:
[0070] S1. By weight, add polyvinyl chloride resin and composite chlorinated polyvinyl chloride masterbatch into a high-speed mixer, heat to 100°C, add composite stabilizer, control the stirring speed to 800 rpm, mix for 10 min, and obtain the initial mixture.
[0071] S2. Add functionalized nano-silica, impact modifier, plasticizer and lubricant to the initial mixture, continue to heat to 120℃, control the stirring speed to 1200rpm, mix for 15min to obtain the mixture.
[0072] S3. Transfer the mixture to a cold mixer, cool it to 40°C, and then discharge it into a twin-screw extruder. The temperature settings for each zone of the twin-screw extruder are: Zone 1 150°C, Zone 2 160°C, Zone 3 170°C, and Die Head 175°C. The screw speed is 150 rpm, and the length-to-diameter ratio is 36:1. After melt blending, granulate it using a water ring pelletizer. The pelletizing speed is set to 300 rpm. After naturally cooling to room temperature, send it to a fluidized bed for drying at 50°C for 30 minutes to obtain high-strength, anti-aging PVC plastic granules.
[0073] Example 3
[0074] A high-strength, anti-aging PVC plastic granule comprises the following raw materials in parts by weight: 80 parts of polyvinyl chloride resin, 40 parts of composite chlorinated polyvinyl chloride masterbatch, 15 parts of functionalized nano silica, 8 parts of impact modifier, 20 parts of plasticizer, 5 parts of composite stabilizer, and 2 parts of lubricant.
[0075] The composite chlorinated polyvinyl chloride masterbatch is made by adding chlorinated polyvinyl chloride, epoxidized natural rubber and zinc stearate into a mixer in a mass ratio of 100:25:2, mixing for 10 minutes at a mixing temperature of 170℃ and a rotor speed of 70rpm, and then extruding.
[0076] Functionalized nano-silica was prepared by the following method:
[0077] (1) The mass ratio of cyanuric chloride, toluene, γ-aminopropyltriethoxysilane, 4-amino-2,2,6,6-tetramethylpiperidine, 4-amino-2,6-di-tert-butylphenol and triethylamine was controlled to be 20:200:23:16:23:35. Triethylamine was divided into three parts. Cyanuric chloride was dissolved in toluene. γ-aminopropyltriethoxysilane and the first part of triethylamine were added dropwise at a constant rate under the conditions of 5℃ ice-water bath and 600rpm stirring. The addition was completed in 1h. After the addition was completed, the system was heated to 50℃ after 2h of reaction. 4-amino-2,2,6,6-tetramethylpiperidine and the second part of triethylamine were added. After 4h of reaction, the temperature was further increased to 90℃. 4-amino-2,6-di-tert-butylphenol and the third part of triethylamine were added. The reaction was continued for 8h. After the reaction was completed, the salt precipitate generated by the reaction was removed by filtration to obtain the functional modified liquid.
[0078] (2) Control the mass ratio of nano-silica and functional modification liquid to 1:4. Put nano-silica with an average particle size of 50nm into a high-speed mixer equipped with a vacuum pump and condensation recovery device, heat it to 120℃ for 15min, keep the temperature constant, and spray deionized water equivalent to 3% of the mass of nano-silica into the high-speed mixer under stirring at 2000rpm. Then spray the functional modification liquid onto the surface of nano-silica and continue high-speed mixing for 15min. During this process, turn on the vacuum pump to remove the solvent and reaction by-products, cool, and obtain functionalized nano-silica.
[0079] The plasticizer is dioctyl terephthalate.
[0080] The composite stabilizer is a calcium-zinc composite stabilizer.
[0081] The lubricant is a mixture of stearic acid and polyethylene wax in a mass ratio of 3:1.
[0082] A method for preparing high-strength, anti-aging PVC plastic granules includes the following steps:
[0083] S1. By weight, add polyvinyl chloride resin and composite chlorinated polyvinyl chloride masterbatch to a high-speed mixer, heat to 110°C, add composite stabilizer, control the stirring speed at 1000 rpm, mix for 5 minutes to obtain the initial mixture.
[0084] S2. Add functionalized nano-silica, impact modifier, plasticizer and lubricant to the initial mixture, continue to heat to 130℃, control the stirring speed at 1500rpm, mix for 10min to obtain the mixture.
[0085] S3. Transfer the mixture to a cold mixer, cool it to 50°C, and then discharge it into a twin-screw extruder. The temperature settings for each zone of the twin-screw extruder are: Zone 1 160°C, Zone 2 170°C, Zone 3 180°C, and Die Head 185°C. The screw speed is 200 rpm, and the length-to-diameter ratio is 40:1. After melt blending, granulate it using a water ring pelletizer. The pelletizing speed is set to 500 rpm. After naturally cooling to room temperature, feed it into a fluidized bed and dry it at 60°C for 20 minutes to obtain high-strength, anti-aging PVC plastic granules.
[0086] To verify the comprehensive performance of the high-strength, anti-aging PVC plastic granules provided by this invention, comparative examples 1-8 were set up, wherein:
[0087] Comparative Example 1
[0088] Comparative Example 1 is the same as Example 1, except that the composite chlorinated polyvinyl chloride masterbatch is used to replace the chlorinated polyvinyl chloride by the same mass. Details are as follows:
[0089] A high-strength, anti-aging PVC plastic granule comprises the following raw materials in parts by weight: 70 parts of polyvinyl chloride resin, 30 parts of chlorinated polyvinyl chloride, 10 parts of functionalized nano silica, 6 parts of impact modifier, 15 parts of plasticizer, 4 parts of composite stabilizer, and 1.5 parts of lubricant.
[0090] The functionalized nano-silica is prepared by the following method:
[0091] (1) The mass ratio of cyanuric chloride, toluene, γ-aminopropyltriethoxysilane, 4-amino-2,2,6,6-tetramethylpiperidine, 4-amino-2,6-di-tert-butylphenol and triethylamine was controlled to be 19:200:22:15.5:22:33. The triethylamine was divided into three parts. Cyanuric chloride was dissolved in toluene. γ-aminopropyltriethoxysilane was added dropwise at a uniform rate under continuous stirring at 500 rpm in an ice-water bath at 3°C. The first part of triethylamine was added dropwise over 1.5 hours. After the addition was complete, the reaction was allowed to proceed for 2.5 hours. Then, the system was heated to 45°C, and 4-amino-2,2,6,6-tetramethylpiperidine and the second part of triethylamine were added. After the reaction was allowed to proceed for 5 hours, the system was heated to 85°C, and 4-amino-2,6-di-tert-butylphenol and the third part of triethylamine were added. The reaction was continued for 9 hours. After the reaction was completed, the salt precipitate generated by the reaction was removed by filtration to obtain the functional modified solution.
[0092] (2) The mass ratio of nano-silica to functional modification liquid is controlled to be 1:3. Nano-silica with an average particle size of 40 nm is put into a high-speed mixer equipped with a vacuum pump and condensation recovery device. The temperature is raised to 115 °C for 13 min and kept constant. Under the stirring state of 1800 rpm, deionized water equivalent to 2% of the mass of nano-silica is sprayed into the high-speed mixer. Then the functional modification liquid is sprayed onto the surface of nano-silica and the mixture is continued to be mixed at high speed for 18 min. During this process, the vacuum pump is turned on to remove the solvent and reaction by-products. After cooling, functionalized nano-silica is obtained.
[0093] The plasticizer is dioctyl terephthalate.
[0094] The composite stabilizer is a calcium-zinc composite stabilizer.
[0095] The lubricant is a mixture of stearic acid and polyethylene wax in a mass ratio of 2:1.
[0096] A method for preparing high-strength, anti-aging PVC plastic granules includes the following steps:
[0097] S1. By weight, add polyvinyl chloride resin and chlorinated polyvinyl chloride into a high-speed mixer, heat to 105°C, add composite stabilizer, control the stirring speed to 900 rpm, mix for 8 minutes to obtain the initial mixture.
[0098] S2. Add functionalized nano-silica, impact modifier, plasticizer and lubricant to the initial mixture, continue to heat to 125℃, control the stirring speed to 1350rpm, mix for 13min to obtain the mixture.
[0099] S3. Transfer the mixture to a cold mixer, cool it to 45°C, and then discharge it into a twin-screw extruder. The temperature settings for each zone of the twin-screw extruder are: Zone 1 155°C, Zone 2 165°C, Zone 3 175°C, and the die head 180°C. The screw speed is 180 rpm, and the length-to-diameter ratio is 38:1. After melt blending, granulate it using a water ring pelletizer. The pelletizing speed is set to 400 rpm. After naturally cooling to room temperature, send it to a fluidized bed for drying at 55°C for 25 minutes to obtain high-strength, anti-aging PVC plastic granules.
[0100] Comparative Example 2
[0101] Comparative Example 2 is the same as Example 1, except that the composite chlorinated polyvinyl chloride masterbatch was produced by internal extrusion mixing of chlorinated polyvinyl chloride and zinc stearate at a mass ratio of 100:1.5. Details are as follows:
[0102] A high-strength, anti-aging PVC plastic granule comprises the following raw materials in parts by weight: 70 parts of polyvinyl chloride resin, 30 parts of composite chlorinated polyvinyl chloride masterbatch, 10 parts of functionalized nano silica, 6 parts of impact modifier, 15 parts of plasticizer, 4 parts of composite stabilizer, and 1.5 parts of lubricant.
[0103] The composite chlorinated polyvinyl chloride masterbatch is produced by mixing chlorinated polyvinyl chloride and zinc stearate in a mass ratio of 100:1.5 in a mixer, mixing at a mixing temperature of 165℃ and a rotor speed of 60rpm for 12.5 minutes, and then extruding.
[0104] Functionalized nano-silica was prepared by the following method:
[0105] (1) The mass ratio of cyanuric chloride, toluene, γ-aminopropyltriethoxysilane, 4-amino-2,2,6,6-tetramethylpiperidine, 4-amino-2,6-di-tert-butylphenol and triethylamine was controlled to be 19:200:22:15.5:22:33. The triethylamine was divided into three parts. Cyanuric chloride was dissolved in toluene. γ-aminopropyltriethoxysilane was added dropwise at a uniform rate under continuous stirring at 500 rpm in an ice-water bath at 3°C. The first part of triethylamine was added dropwise over 1.5 hours. After the addition was complete, the reaction was allowed to proceed for 2.5 hours. Then, the system was heated to 45°C, and 4-amino-2,2,6,6-tetramethylpiperidine and the second part of triethylamine were added. After the reaction was allowed to proceed for 5 hours, the system was heated to 85°C, and 4-amino-2,6-di-tert-butylphenol and the third part of triethylamine were added. The reaction was continued for 9 hours. After the reaction was completed, the salt precipitate generated by the reaction was removed by filtration to obtain the functional modified solution.
[0106] (2) The mass ratio of nano-silica to functional modification liquid is controlled to be 1:3. Nano-silica with an average particle size of 40 nm is put into a high-speed mixer equipped with a vacuum pump and condensation recovery device. The temperature is raised to 115 °C for 13 min and kept constant. Under the stirring state of 1800 rpm, deionized water equivalent to 2% of the mass of nano-silica is sprayed into the high-speed mixer. Then the functional modification liquid is sprayed onto the surface of nano-silica and the mixture is continued to be mixed at high speed for 18 min. During this process, the vacuum pump is turned on to remove the solvent and reaction by-products. After cooling, functionalized nano-silica is obtained.
[0107] The plasticizer is dioctyl terephthalate.
[0108] The composite stabilizer is a calcium-zinc composite stabilizer.
[0109] The lubricant is a mixture of stearic acid and polyethylene wax in a mass ratio of 2:1.
[0110] A method for preparing high-strength, anti-aging PVC plastic granules includes the following steps:
[0111] S1. By weight, add polyvinyl chloride resin and composite chlorinated polyvinyl chloride masterbatch into a high-speed mixer, heat to 105°C, add composite stabilizer, control the stirring speed to 900 rpm, mix for 8 minutes to obtain the initial mixture.
[0112] S2. Add functionalized nano-silica, impact modifier, plasticizer and lubricant to the initial mixture, continue to heat to 125℃, control the stirring speed to 1350rpm, mix for 13min to obtain the mixture.
[0113] S3. Transfer the mixture to a cold mixer, cool it to 45°C, and then discharge it into a twin-screw extruder. The temperature settings for each zone of the twin-screw extruder are: Zone 1 155°C, Zone 2 165°C, Zone 3 175°C, and the die head 180°C. The screw speed is 180 rpm, and the length-to-diameter ratio is 38:1. After melt blending, granulate it using a water ring pelletizer. The pelletizing speed is set to 400 rpm. After naturally cooling to room temperature, send it to a fluidized bed for drying at 55°C for 25 minutes to obtain high-strength, anti-aging PVC plastic granules.
[0114] Comparative Example 3
[0115] Comparative Example 3 is the same as Example 1, except that the same mass of the composite chlorinated polyvinyl chloride masterbatch is replaced with a mixture of chlorinated polyvinyl chloride, epoxidized natural rubber, and zinc stearate in a mass ratio of 100:20:1.5. Specifically:
[0116] A high-strength, anti-aging PVC plastic granule comprises the following raw materials in parts by weight: 70 parts of polyvinyl chloride resin, 30 parts of composite chlorinated polyvinyl chloride masterbatch, 10 parts of functionalized nano silica, 6 parts of impact modifier, 15 parts of plasticizer, 4 parts of composite stabilizer, and 1.5 parts of lubricant.
[0117] The composite chlorinated polyvinyl chloride masterbatch is made by adding chlorinated polyvinyl chloride, epoxidized natural rubber and zinc stearate into a mixer at a mass ratio of 100:20:1.5 and mixing for 15 minutes at a stirring speed of 300 rpm.
[0118] Functionalized nano-silica was prepared by the following method:
[0119] (1) The mass ratio of cyanuric chloride, toluene, γ-aminopropyltriethoxysilane, 4-amino-2,2,6,6-tetramethylpiperidine, 4-amino-2,6-di-tert-butylphenol and triethylamine was controlled to be 19:200:22:15.5:22:33. The triethylamine was divided into three parts. Cyanuric chloride was dissolved in toluene. γ-aminopropyltriethoxysilane was added dropwise at a uniform rate under continuous stirring at 500 rpm in an ice-water bath at 3°C. The first part of triethylamine was added dropwise over 1.5 hours. After the addition was complete, the reaction was allowed to proceed for 2.5 hours. Then, the system was heated to 45°C, and 4-amino-2,2,6,6-tetramethylpiperidine and the second part of triethylamine were added. After the reaction was allowed to proceed for 5 hours, the system was heated to 85°C, and 4-amino-2,6-di-tert-butylphenol and the third part of triethylamine were added. The reaction was continued for 9 hours. After the reaction was completed, the salt precipitate generated by the reaction was removed by filtration to obtain the functional modified solution.
[0120] (2) The mass ratio of nano-silica to functional modification liquid is controlled to be 1:3. Nano-silica with an average particle size of 40 nm is put into a high-speed mixer equipped with a vacuum pump and condensation recovery device. The temperature is raised to 115 °C for 13 min and kept constant. Under the stirring state of 1800 rpm, deionized water equivalent to 2% of the mass of nano-silica is sprayed into the high-speed mixer. Then the functional modification liquid is sprayed onto the surface of nano-silica and the mixture is continued to be mixed at high speed for 18 min. During this process, the vacuum pump is turned on to remove the solvent and reaction by-products. After cooling, functionalized nano-silica is obtained.
[0121] The plasticizer is dioctyl terephthalate.
[0122] The composite stabilizer is a calcium-zinc composite stabilizer.
[0123] The lubricant is a mixture of stearic acid and polyethylene wax in a mass ratio of 2:1.
[0124] A method for preparing high-strength, anti-aging PVC plastic granules includes the following steps:
[0125] S1. By weight, add polyvinyl chloride resin and composite chlorinated polyvinyl chloride masterbatch into a high-speed mixer, heat to 105°C, add composite stabilizer, control the stirring speed to 900 rpm, mix for 8 minutes to obtain the initial mixture.
[0126] S2. Add functionalized nano-silica, impact modifier, plasticizer and lubricant to the initial mixture, continue to heat to 125℃, control the stirring speed to 1350rpm, mix for 13min to obtain the mixture.
[0127] S3. Transfer the mixture to a cold mixer, cool it to 45°C, and then discharge it into a twin-screw extruder. The temperature settings for each zone of the twin-screw extruder are: Zone 1 155°C, Zone 2 165°C, Zone 3 175°C, and the die head 180°C. The screw speed is 180 rpm, and the length-to-diameter ratio is 38:1. After melt blending, granulate it using a water ring pelletizer. The pelletizing speed is set to 400 rpm. After naturally cooling to room temperature, send it to a fluidized bed for drying at 55°C for 25 minutes to obtain high-strength, anti-aging PVC plastic granules.
[0128] Comparative Example 4
[0129] Comparative Example 4 is the same as Example 1, except that functionalized nano-silica is replaced with nano-silica of equal mass. Details are as follows:
[0130] A high-strength, anti-aging PVC plastic granule comprises the following raw materials in parts by weight: 70 parts of polyvinyl chloride resin, 30 parts of composite chlorinated polyvinyl chloride masterbatch, 10 parts of nano silica, 6 parts of impact modifier, 15 parts of plasticizer, 4 parts of composite stabilizer, and 1.5 parts of lubricant.
[0131] The composite chlorinated polyvinyl chloride masterbatch is made by adding chlorinated polyvinyl chloride, epoxidized natural rubber and zinc stearate into a mixer in a mass ratio of 100:20:1.5, mixing at a mixing temperature of 165℃ and a rotor speed of 60rpm for 12.5 minutes, and then extruding.
[0132] The average particle size of nano-silica is 40 nm.
[0133] The plasticizer is dioctyl terephthalate.
[0134] The composite stabilizer is a calcium-zinc composite stabilizer.
[0135] The lubricant is a mixture of stearic acid and polyethylene wax in a mass ratio of 2:1.
[0136] A method for preparing high-strength, anti-aging PVC plastic granules includes the following steps:
[0137] S1. By weight, add polyvinyl chloride resin and composite chlorinated polyvinyl chloride masterbatch into a high-speed mixer, heat to 105°C, add composite stabilizer, control the stirring speed to 900 rpm, mix for 8 minutes to obtain the initial mixture.
[0138] S2. Add nano silica, impact modifier, plasticizer and lubricant to the initial mixture, continue to heat to 125℃, control the stirring speed to 1350rpm, mix for 13min to obtain the mixture.
[0139] S3. Transfer the mixture to a cold mixer, cool it to 45°C, and then discharge it into a twin-screw extruder. The temperature settings for each zone of the twin-screw extruder are: Zone 1 155°C, Zone 2 165°C, Zone 3 175°C, and the die head 180°C. The screw speed is 180 rpm, and the length-to-diameter ratio is 38:1. After melt blending, granulate it using a water ring pelletizer. The pelletizing speed is set to 400 rpm. After naturally cooling to room temperature, send it to a fluidized bed for drying at 55°C for 25 minutes to obtain high-strength, anti-aging PVC plastic granules.
[0140] Comparative Example 5
[0141] Comparative Example 5 is the same as Example 1, except that the preparation method of the functionalized nano-silica is different. Details are as follows:
[0142] A high-strength, anti-aging PVC plastic granule comprises the following raw materials in parts by weight: 70 parts of polyvinyl chloride resin, 30 parts of composite chlorinated polyvinyl chloride masterbatch, 10 parts of functionalized nano silica, 6 parts of impact modifier, 15 parts of plasticizer, 4 parts of composite stabilizer, and 1.5 parts of lubricant.
[0143] The composite chlorinated polyvinyl chloride masterbatch is made by adding chlorinated polyvinyl chloride, epoxidized natural rubber and zinc stearate into a mixer in a mass ratio of 100:20:1.5, mixing at a mixing temperature of 165℃ and a rotor speed of 60rpm for 12.5 minutes, and then extruding.
[0144] Functionalized nano-silica was prepared by the following method:
[0145] (1) The mass ratio of toluene, γ-aminopropyltriethoxysilane, 4-amino-2,2,6,6-tetramethylpiperidine, 4-amino-2,6-di-tert-butylphenol and triethylamine was controlled to be 200:22:15.5:22:33. Triethylamine was divided into three parts. γ-aminopropyltriethoxysilane and the first part of triethylamine were added dropwise to toluene at a constant rate under continuous stirring at 500 rpm in an ice-water bath at 3 ℃. The addition was completed in 1.5 h. After the addition was completed, the mixture was stirred for 2.5 h. The system was then heated to 45 ℃, and 4-amino-2,2,6,6-tetramethylpiperidine and the second part of triethylamine were added. After stirring for 5 h, the system was further heated to 85 ℃, and 4-amino-2,6-di-tert-butylphenol and the third part of triethylamine were added. The mixture was stirred for 9 h. After the mixing was completed, the functional modified liquid was obtained.
[0146] (2) Control the mass ratio of nano-silica and functional modification liquid to 1:3. Put nano-silica with an average particle size of 40nm into a high-speed mixer equipped with a vacuum pump and condensation recovery device, heat it to 115℃ for 13min, keep the temperature constant, and spray deionized water equivalent to 2% of the mass of nano-silica into the high-speed mixer under stirring at 1800rpm. Then spray the functional modification liquid onto the surface of nano-silica and continue high-speed mixing for 18min. During this process, turn on the vacuum pump to remove the solvent and reaction by-products, cool, and obtain functionalized nano-silica.
[0147] The plasticizer is dioctyl terephthalate.
[0148] The composite stabilizer is a calcium-zinc composite stabilizer.
[0149] The lubricant is a mixture of stearic acid and polyethylene wax in a mass ratio of 2:1.
[0150] A method for preparing high-strength, anti-aging PVC plastic granules includes the following steps:
[0151] S1. By weight, add polyvinyl chloride resin and composite chlorinated polyvinyl chloride masterbatch into a high-speed mixer, heat to 105°C, add composite stabilizer, control the stirring speed to 900 rpm, mix for 8 minutes to obtain the initial mixture.
[0152] S2. Add functionalized nano-silica, impact modifier, plasticizer and lubricant to the initial mixture, continue to heat to 125℃, control the stirring speed to 1350rpm, mix for 13min to obtain the mixture.
[0153] S3. Transfer the mixture to a cold mixer, cool it to 45°C, and then discharge it into a twin-screw extruder. The temperature settings for each zone of the twin-screw extruder are: Zone 1 155°C, Zone 2 165°C, Zone 3 175°C, and the die head 180°C. The screw speed is 180 rpm, and the length-to-diameter ratio is 38:1. After melt blending, granulate it using a water ring pelletizer. The pelletizing speed is set to 400 rpm. After naturally cooling to room temperature, send it to a fluidized bed for drying at 55°C for 25 minutes to obtain high-strength, anti-aging PVC plastic granules.
[0154] Comparative Example 6
[0155] Comparative Example 6 is the same as Example 1, except that the preparation method of the functionalized nano-silica is different. Details are as follows:
[0156] A high-strength, anti-aging PVC plastic granule comprises the following raw materials in parts by weight: 70 parts of polyvinyl chloride resin, 30 parts of composite chlorinated polyvinyl chloride masterbatch, 10 parts of functionalized nano silica, 6 parts of impact modifier, 15 parts of plasticizer, 4 parts of composite stabilizer, and 1.5 parts of lubricant.
[0157] The composite chlorinated polyvinyl chloride masterbatch is made by adding chlorinated polyvinyl chloride, epoxidized natural rubber and zinc stearate into a mixer in a mass ratio of 100:20:1.5, mixing at a mixing temperature of 165℃ and a rotor speed of 60rpm for 12.5 minutes, and then extruding.
[0158] Functionalized nano-silica was prepared by the following method:
[0159] (1) The mass ratio of cyanuric chloride, toluene, γ-aminopropyltriethoxysilane, 4-amino-2,6-di-tert-butylphenol and triethylamine was controlled to be 19:200:22:22:22. Triethylamine was divided into two parts. Cyanuric chloride was dissolved in toluene. γ-aminopropyltriethoxysilane and the first part of triethylamine were added dropwise at a constant rate under the conditions of 3℃ ice-water bath and 500rpm stirring. The addition was completed in 1.5h. After the addition was completed, the reaction was carried out for 2.5h. The system was then heated to 85℃ and 4-amino-2,6-di-tert-butylphenol and the second part of triethylamine were added. The reaction was continued for 9h. After the reaction was completed, the salt precipitate generated by the reaction was removed by filtration to obtain the functional modified liquid.
[0160] (2) Control the mass ratio of nano-silica and functional modification liquid to 1:3. Put nano-silica with an average particle size of 40nm into a high-speed mixer equipped with a vacuum pump and condensation recovery device, heat it to 115℃ for 13min, keep the temperature constant, and spray deionized water equivalent to 2% of the mass of nano-silica into the high-speed mixer under stirring at 1800rpm. Then spray the functional modification liquid onto the surface of nano-silica and continue high-speed mixing for 18min. During this process, turn on the vacuum pump to remove the solvent and reaction by-products, cool, and obtain functionalized nano-silica.
[0161] The plasticizer is dioctyl terephthalate.
[0162] The composite stabilizer is a calcium-zinc composite stabilizer.
[0163] The lubricant is a mixture of stearic acid and polyethylene wax in a mass ratio of 2:1.
[0164] A method for preparing high-strength, anti-aging PVC plastic granules includes the following steps:
[0165] S1. By weight, add polyvinyl chloride resin and composite chlorinated polyvinyl chloride masterbatch into a high-speed mixer, heat to 105°C, add composite stabilizer, control the stirring speed to 900 rpm, mix for 8 minutes to obtain the initial mixture.
[0166] S2. Add functionalized nano-silica, impact modifier, plasticizer and lubricant to the initial mixture, continue to heat to 125℃, control the stirring speed to 1350rpm, mix for 13min to obtain the mixture.
[0167] S3. Transfer the mixture to a cold mixer, cool it to 45°C, and then discharge it into a twin-screw extruder. The temperature settings for each zone of the twin-screw extruder are: Zone 1 155°C, Zone 2 165°C, Zone 3 175°C, and the die head 180°C. The screw speed is 180 rpm, and the length-to-diameter ratio is 38:1. After melt blending, granulate it using a water ring pelletizer. The pelletizing speed is set to 400 rpm. After naturally cooling to room temperature, send it to a fluidized bed for drying at 55°C for 25 minutes to obtain high-strength, anti-aging PVC plastic granules.
[0168] Comparative Example 7
[0169] Comparative Example 7 is the same as Example 1, except that the preparation method of the functionalized nano-silica is different. Details are as follows:
[0170] A high-strength, anti-aging PVC plastic granule comprises the following raw materials in parts by weight: 70 parts of polyvinyl chloride resin, 30 parts of composite chlorinated polyvinyl chloride masterbatch, 10 parts of functionalized nano silica, 6 parts of impact modifier, 15 parts of plasticizer, 4 parts of composite stabilizer, and 1.5 parts of lubricant.
[0171] The composite chlorinated polyvinyl chloride masterbatch is made by adding chlorinated polyvinyl chloride, epoxidized natural rubber and zinc stearate into a mixer in a mass ratio of 100:20:1.5, mixing at a mixing temperature of 165℃ and a rotor speed of 60rpm for 12.5 minutes, and then extruding.
[0172] Functionalized nano-silica was prepared by the following method:
[0173] (1) The mass ratio of cyanuric chloride, toluene, γ-aminopropyltriethoxysilane, 4-amino-2,2,6,6-tetramethylpiperidine, aniline and triethylamine was controlled to be 19:200:22:15.5:9:33. Triethylamine was divided into three parts. Cyanuric chloride was dissolved in toluene. γ-aminopropyltriethoxysilane and the first part of triethylamine were added dropwise at a constant rate under the conditions of 3℃ ice-water bath and 500rpm stirring. The addition was completed in 1.5h. After the addition was completed, the reaction was carried out for 2.5h. The system was then heated to 45℃. 4-amino-2,2,6,6-tetramethylpiperidine and the second part of triethylamine were added. After the reaction was carried out for 5h, the temperature was further raised to 85℃. Aniline and the third part of triethylamine were added. The reaction was continued for 9h. After the reaction was completed, the salt precipitate generated by the reaction was removed by filtration to obtain the functional modified liquid.
[0174] (2) The mass ratio of nano-silica to functional modification liquid is controlled to be 1:3. Nano-silica with an average particle size of 40 nm is put into a high-speed mixer equipped with a vacuum pump and condensation recovery device. The temperature is raised to 115 °C for 13 min and kept constant. Under the stirring state of 1800 rpm, deionized water equivalent to 2% of the mass of nano-silica is sprayed into the high-speed mixer. Then the functional modification liquid is sprayed onto the surface of nano-silica and the mixture is continued to be mixed at high speed for 18 min. During this process, the vacuum pump is turned on to remove the solvent and reaction by-products. After cooling, functionalized nano-silica is obtained.
[0175] The plasticizer is dioctyl terephthalate.
[0176] The composite stabilizer is a calcium-zinc composite stabilizer.
[0177] The lubricant is a mixture of stearic acid and polyethylene wax in a mass ratio of 2:1.
[0178] A method for preparing high-strength, anti-aging PVC plastic granules includes the following steps:
[0179] S1. By weight, add polyvinyl chloride resin and composite chlorinated polyvinyl chloride masterbatch into a high-speed mixer, heat to 105°C, add composite stabilizer, control the stirring speed to 900 rpm, mix for 8 minutes to obtain the initial mixture.
[0180] S2. Add functionalized nano-silica, impact modifier, plasticizer and lubricant to the initial mixture, continue to heat to 125℃, control the stirring speed to 1350rpm, mix for 13min to obtain the mixture.
[0181] S3. Transfer the mixture to a cold mixer, cool it to 45°C, and then discharge it into a twin-screw extruder. The temperature settings for each zone of the twin-screw extruder are: Zone 1 155°C, Zone 2 165°C, Zone 3 175°C, and the die head 180°C. The screw speed is 180 rpm, and the length-to-diameter ratio is 38:1. After melt blending, granulate it using a water ring pelletizer. The pelletizing speed is set to 400 rpm. After naturally cooling to room temperature, send it to a fluidized bed for drying at 55°C for 25 minutes to obtain high-strength, anti-aging PVC plastic granules.
[0182] Comparative Example 8
[0183] Comparative Example 8 is the same as Example 1, except that the functionalized nano-silica is replaced by a mixture of nano-silica by mass. Details are as follows:
[0184] A high-strength, anti-aging PVC plastic granule comprises the following raw materials in parts by weight: 70 parts of polyvinyl chloride resin, 30 parts of composite chlorinated polyvinyl chloride masterbatch, 10 parts of nano silica mixture, 6 parts of impact modifier, 15 parts of plasticizer, 4 parts of composite stabilizer, and 1.5 parts of lubricant.
[0185] The composite chlorinated polyvinyl chloride masterbatch is made by adding chlorinated polyvinyl chloride, epoxidized natural rubber and zinc stearate into a mixer in a mass ratio of 100:20:1.5, mixing at a mixing temperature of 165℃ and a rotor speed of 60rpm for 12.5 minutes, and then extruding.
[0186] The nano-silica mixture was prepared by the following method: nano-silica with an average particle size of 40 nm, 4-amino-2,2,6,6-tetramethylpiperidine and 4-amino-2,6-di-tert-butylphenol were added to a mixer in a mass ratio of 10:1.6:2.2 and stirred for 40 min at a stirring speed of 500 rpm.
[0187] The plasticizer is dioctyl terephthalate.
[0188] The composite stabilizer is a calcium-zinc composite stabilizer.
[0189] The lubricant is a mixture of stearic acid and polyethylene wax in a mass ratio of 2:1.
[0190] A method for preparing high-strength, anti-aging PVC plastic granules includes the following steps:
[0191] S1. By weight, add polyvinyl chloride resin and composite chlorinated polyvinyl chloride masterbatch into a high-speed mixer, heat to 105°C, add composite stabilizer, control the stirring speed to 900 rpm, mix for 8 minutes to obtain the initial mixture.
[0192] S2. Add nano-silica mixture, impact modifier, plasticizer and lubricant to the initial mixture, continue to heat to 125℃, control the stirring speed to 1350rpm, mix for 13min to obtain the mixture.
[0193] S3. Transfer the mixture to a cold mixer, cool it to 45°C, and then discharge it into a twin-screw extruder. The temperature settings for each zone of the twin-screw extruder are: Zone 1 155°C, Zone 2 165°C, Zone 3 175°C, and the die head 180°C. The screw speed is 180 rpm, and the length-to-diameter ratio is 38:1. After melt blending, granulate it using a water ring pelletizer. The pelletizing speed is set to 400 rpm. After naturally cooling to room temperature, send it to a fluidized bed for drying at 55°C for 25 minutes to obtain high-strength, anti-aging PVC plastic granules.
[0194] Performance testing
[0195] The comprehensive performance of the high-strength, anti-aging PVC plastic granules prepared in Examples 1-3 and Comparative Examples 1-8 was tested respectively.
[0196] 1. Mechanical properties: The tensile strength and elongation at break of the specimens were tested in accordance with the national standard GB / T 1040.2-2022 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics". The specimens were made by injection molding PVC plastic granules into dumbbell-shaped specimens conforming to the standard using an injection molding machine, and the injection temperature was set to 175℃.
[0197] 2. Electrical insulation performance: The volume resistivity of the sample was tested at 20℃ in accordance with the national standard GB / T 31838.2-2019 "Dielectric and resistive properties of solid insulating materials - Part 2: Resistive properties (DC method) - Volume resistivity and volume resistivity". The sample was hot-pressed into a 1mm thick circular sample by a flat vulcanizing machine at 175℃ for testing.
[0198] 3. Anti-aging performance test: According to GB / T 16422.3-2022 "Laboratory Light Source Exposure Test Method for Plastics Part 3: Fluorescent Ultraviolet Lamp", the sample was placed in a QUV ultraviolet aging test chamber (the sample used was the same type 1A dumbbell-shaped injection molded sample as the one used for mechanical performance testing). A UVB-313 lamp was set, the irradiance was 0.71W / m², the cycle was 8h of irradiation at 60℃ + 4h of condensation at 50℃, and after 1000 hours of continuous operation, the tensile strength after aging was tested, and the tensile strength retention rate after aging (%) was calculated as (tensile strength after aging / initial tensile strength) × 100%; at the same time, the total color difference (ΔE) before and after aging was measured using a CIE Lab colorimeter (the larger the ΔE, the more severe the yellowing); and the surface precipitation (blooming) was observed.
[0199] The test results are shown in Table 1:
[0200] Table 1:
[0201] Test Project Tensile strength (MPa) Elongation at break (%) <![CDATA[Volume resistivity (10 14 Ω·m)]]> Tensile strength retention rate after aging (%) Color difference after aging (ΔE) Surface blooming (blooming) Example 1 41.2 265 17.5 94.5 1.85 none Example 2 40.5 272 17.8 93.8 1.92 none Example 3 42.5 258 18.2 95.1 1.68 none Comparative Example 1 34.6 195 15.1 82.4 4.45 none Comparative Example 2 35.2 198 15.3 88.7 2.38 none Comparative Example 3 37.8 220 16.5 92.1 1.56 none Comparative Example 4 38.5 250 18.1 61.4 9.75 none Comparative Example 5 36.2 245 8.6 76.5 4.85 There is a spray. Comparative Example 6 41.0 262 16.4 79.8 5.42 none Comparative Example 7 40.8 260 16.2 87.5 3.85 none Comparative Example 8 35.5 255 5.4 68.3 6.15 Severe precipitation
[0202] As shown in Table 1, the high-strength anti-aging PVC plastic granules prepared in Examples 1-3 of this invention maintain excellent levels in all mechanical properties, electrical insulation properties and anti-aging properties, and their overall performance is significantly better than that of Comparative Examples 1-8.
[0203] As can be seen from Example 1 and Comparative Examples 1 and 2, both Comparative Examples 1 and 2 lack epoxidized natural rubber components, resulting in a lack of in-situ acid absorption and interfacial crosslinking during the extrusion process. Therefore, the tensile strength and elongation at break of both components significantly decreased. Furthermore, the lack of epoxidized natural rubber's ability to capture hydrogen chloride during aging led to accelerated degradation, resulting in a significant decrease in tensile strength retention and increased color difference after aging.
[0204] As can be seen from Example 1 and Comparative Example 3, although Comparative Example 3 contains the same raw material components as Example 1, it does not undergo pre-mixing and extrusion, but only simple physical mixing. As a result, the epoxidized natural rubber cannot be fully pre-dispersed and react in situ under high temperature and high shear mixing environment. The interfacial bonding force between the matrices is weaker than that in Example 1, which leads to a certain degree of degradation in mechanical properties and anti-aging properties.
[0205] As can be seen from Example 1 and Comparative Example 4, Comparative Example 4 used unmodified ordinary nano-silica, which lacks surface-grafted anti-aging groups. Although rigid particles can provide some mechanical reinforcement, under long-term ultraviolet light irradiation and thermo-oxidative effects, the system lacks an effective free radical trapping mechanism, resulting in a significant decrease in tensile strength retention after aging and yellowing.
[0206] As can be seen from Example 1 and Comparative Example 5, Comparative Example 5 did not add cyanuric chloride bridging agent during the preparation of modified nano-silica, which prevented the hindered amine and hindered phenol from being covalently immobilized on the surface of nano-silica, and they existed only in a free state. These free small molecules easily migrate within the material and precipitate onto the surface, leading to significant blooming, which in turn damages the insulating layer and causes a substantial decrease in volume resistivity. Simultaneously, due to the loss of effective components with precipitation, the anti-aging performance is significantly inferior to that of Example 1.
[0207] As shown in Example 1 and Comparative Examples 6 and 7, Comparative Example 6 did not have hindered amine groups grafted onto it, and Comparative Example 7 did not have hindered phenol groups grafted onto it. The test results indicate that a single antioxidant group or a single light-stabilizing group cannot provide comprehensive long-term protection. Ultimately, the tensile strength retention rate and color difference of both after aging are inferior to those of Example 1, which has both photothermal anti-aging groups.
[0208] As can be seen from Example 1 and Comparative Example 8, Comparative Example 8 uses direct physical blending of nano-silica with free hindered amines and hindered phenols. Due to the internal plasticizing effect of small molecule additives, the initial tensile strength is lower than that of Example 1. At the same time, severe migration of free small molecules causes severe blooming, which significantly deteriorates the electrical insulation performance. Furthermore, the anti-aging protection performance is reduced due to the loss of anti-aging components during aging tests.
[0209] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A high-strength, anti-aging PVC plastic granule, characterized in that, The raw materials include the following parts by weight: 60-80 parts of polyvinyl chloride resin, 20-40 parts of composite chlorinated polyvinyl chloride masterbatch, 5-15 parts of functionalized nano silica, 4-8 parts of impact modifier, 10-20 parts of plasticizer, 3-5 parts of composite stabilizer, and 1-2 parts of lubricant.
2. The high-strength, anti-aging PVC plastic granules according to claim 1, characterized in that, The composite chlorinated polyvinyl chloride masterbatch is produced by intensive extrusion of chlorinated polyvinyl chloride, epoxidized natural rubber and zinc stearate in a mass ratio of 100:15-25:1-2.
3. The high-strength, anti-aging PVC plastic granules according to claim 1, characterized in that, The functionalized nano-silica is modified nano-silica with hindered amine groups and hindered phenolic groups covalently grafted onto its surface through a triazine ring structure.
4. The high-strength, anti-aging PVC plastic granules according to claim 3, characterized in that, The functionalized nano-silica was prepared by the following method: (1) Dissolve cyanuric chloride in toluene, and add γ-aminopropyltriethoxysilane and the first part of organic acid binder dropwise under an ice-water bath at 0-5℃. After the addition is complete, react for 2-3 hours, then heat the system to 40-50℃, add 4-amino-2,2,6,6-tetramethylpiperidine and the second part of organic acid binder, and react for 4-6 hours. Then heat the system to 80-90℃, add 4-amino-2,6-di-tert-butylphenol and the third part of organic acid binder, and continue the reaction for 8-10 hours. After the reaction is complete, filter to remove the salt precipitate generated in the reaction to obtain the functional modified liquid. (2) Put nano-silica into a high-speed mixer equipped with a vacuum pump and condensation recovery device, heat it to 110-120℃ for 10-15 min, keep the temperature constant, and spray deionized water equivalent to 1-3% of the mass of nano-silica into the high-speed mixer while stirring. Then spray the functional modification liquid onto the surface of nano-silica and continue high-speed mixing for 15-20 min. During this process, turn on the vacuum pump to remove the solvent and reaction by-products, cool, and obtain functionalized nano-silica.
5. The high-strength, anti-aging PVC plastic granules according to claim 4, characterized in that, In step (1), the organic acid binder is triethylamine.
6. The high-strength, anti-aging PVC plastic granules according to claim 5, characterized in that, In step (1), the mass ratio of cyanuric chloride, toluene, γ-aminopropyltriethoxysilane, 4-amino-2,2,6,6-tetramethylpiperidine, 4-amino-2,6-di-tert-butylphenol and the total amount of organic acid binder is 18-20:200:21-23:15-16:21-23:31-35, and the mass ratio of the first part of organic acid binder, the second part of organic acid binder and the third part of organic acid binder is 1:1:
1.
7. The high-strength, anti-aging PVC plastic granules according to claim 4, characterized in that, In step (1), dripping refers to the process of adding the substance at a constant speed under continuous stirring at 400-600 rpm, and completing the dripping process in 1-2 hours.
8. The high-strength, anti-aging PVC plastic granules according to claim 4, characterized in that, In step (2), the mass ratio of nano-silica to functional modification liquid is 1:2-4.
9. The high-strength, anti-aging PVC plastic granules according to claim 1, characterized in that, The lubricant is a mixture of stearic acid and polyethylene wax in a mass ratio of 1-3:
1.
10. A method for preparing high-strength, anti-aging PVC plastic granules according to any one of claims 1-9, characterized in that, Includes the following steps: S1. By weight, add polyvinyl chloride resin and composite chlorinated polyvinyl chloride masterbatch into a high-speed mixer, heat to 100-110℃, add composite stabilizer and mix to obtain initial mixture; S2. Add functionalized nano-silica, impact modifier, plasticizer and lubricant to the initial mixture, and continue to heat to 120-130℃ to mix, to obtain the mixture. S3. Transfer the mixture to a cold mixer, cool it to 40-50℃, and then send it to a twin-screw extruder for melt blending, extrusion granulation, cooling and drying to obtain high-strength, anti-aging PVC plastic granules.